Application of medical physical culture at extensive superficial burns of the I–II degree - Мелешков В’ячеслав Олександрович (Vjacheslav Meleshkov) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to study and prove purpose of medical physical culture at extensive superficial burns of the I–II degree for normalization of exchange processes, the prevention of the developments of stagnation connected with the compelled decrease in physical activity. Material and Methods: analysis and generalization of scientific and methodical literature. Results: the main means of physical rehabilitation – medical physical culture is considered; its application at treatment of patients with extensive superficial burns of the I–II degree is proved; techniques of medical physical culture in the period of little burn shock and in the period of a sharp toksemy are described in detail. Conclusions: it is established that occupation duration remedial gymnastics depends on a condition of the patient and objectives. In each occupation the all-strengthening, breathing and special exercises, as a rule, have to be applied. The most important feature of a technique of occupations at a burn disease is need of repeated performance during the day of the special exercises directed on prevention or elimination of malfunction of the musculoskeletal device.